Environmental Modelling through Chaotic Approach: A Case Study on Ozone and Temperature Time Series - Abd Hamid, Nor Zila; ., . (International Journal of Engineering and Technology, 2018)
The main objective of this study is to develop a suitable model for analysing and predicting environmental variable. Since O3 pollution is harmful and the changes in temperature can have serious consequences to health, therefore, both variables are chosen. Tanjong Malim, a semi-urban educational area located in Perak Malaysia is selected since it is well known that educational area is frequently visited by peoples. Thus, the environmental modelling is necessary. Analysis by the phase space plot and Cao method shown that the chaotic nature presents in both observed time series. Hence, both time series are predicted through the chaotic approach. Results from the local mean approximation method shown that both time series are predicted well with correlation coefficient near to one. Therefore, chaotic approach is suitable to be applied in environmental modelling. These findings are expected to help stakeholders such as Ministry of Education, Meteorological Department and Department of Environment in having a better environment management.Â Â